Penguatan Layanan Cybercounseling pada Pasca Pandemi Covid-19 - Prihmaningrum AM, Vici (Assertive: Islamic Counseling Journal, 2022)
Cyber counseling services occur when the counselee and counselee communicate remotely via a device connected to the internet network. This service provided significant results in the effectiveness of guidance and counseling assistance during the Covid-19 pandemic. In the post-covid-19 pandemic, cybercounseling services are still a choice for counseling services. The needs of each individual adapt to new normal conditions with technological sophistication capital. Strengthening cybercounseling services is needed so that it can more optimally achieve the goals of the counseling program. This study aims to explain the Strengthening of Cybercounseling Services in the Post-Covid-19 Pandemic. For this study, a literature review was used to collect primary data from literature relevant to the subject and supported by secondary sources to fulfill the procedures in data analysis. The results of this study show several strategies for strengthening cybercounseling services that can be carried out, including (1) Understanding and implementing ethics; (2) Mastery and skill of cybercounseling service media; and (3) Monitoring and evaluation.